Effect of supplementary zinc from organic and inorganic sources on laying performance and zinc deposition in eggs - Hatairat Plaimast (2018)
The experiment was conducted to investigate the effect of supplementary organic and inorganic zinc on the laying performance and zinc deposition in eggs. One hundred and eighty laying hens (ISA Brown), aged 36 weeks, were randomly divided into 5 treatments with 4 replications of 9 hens each. A corn-soy based diet which was formulated to meet the recommended nutrient requirement especially the level of zinc (60 μg Zn/g diet) was used as the control diet. Both sources of zinc, inorganic (zinc sulfate) and organic (zinc amino acid chelate) were supplemented to provide zinc at levels of 300 and 600 μg/g diet, respectively. Supplementation of both the forms and levels of zinc in hens' diet had no effect on egg production, egg weight, the amount of feed consumed and feed per kg egg (p>0.05). Increasing the zinc level in the diet increased zinc deposition in the egg yolk (p<0.01). Ninety-nine percentage of the zinc was deposited in the egg yolk. A very low level of zinc was deposited in the egg white and the level seemed to be constant. No significant difference in the level of zinc deposition in the yolk was found between the organic and inorganic form of zinc. The forms and the levels of zinc supplemented also did not affect the quality of egg.